Continuous Films of Self‐Assembled Graphene Quantum Dots for n‐Type Doping of Graphene by UV‐Triggered Charge Transfer. Issue 35 (16th January 2017) - Park, Myung Jin; Kim, Yuna; Kim, Youngsoo; Hong, Byung Hee
Abstract : The demands to examine components serving as one of the active layers in heterostructures of 2D materials have been recently increasing. Nanomaterials synthesized from a solution process and their self‐assembly can provide a promising route to build a new type of mixed dimensional heterostructures, and several methodologies have been reported previously to construct 2D assemblies from colloidal nanostructures in solution. Graphene quantum dots (GQDs), receiving much interest due to the tunable optical band gap and the capability of chemical functionalization, are considered as emerging nanomaterials for various optoelectronic and biological applications. This study fabricates a closely packed GQDs film (GQDF) from colloidal solutions using a solvent‐assisted Langmuir Blodgett method, and investigates the optical and electrical characteristics of the heterostacked graphene/GQD film (G/GQDF) structures. It is observed that the GQDF plays a role not only as a buffer layer that isolates Chemical Vapor Deposited graphene (CVD graphene) from undesired p‐doping but also as a photoactive layer that triggers n‐doping of the heterostacked CVD graphene film. The n‐doping density of the G/GQDF device is proportional to UV irradiation time, but its carrier mobility remains constant regardless of doping densities, which are unique characteristics that have not been observed in other doping methods. Abstract : A closely packed continuous film of graphene quantum dots (GQDF) is demonstrated for utilization in mixed dimensional heterostructures. In a hetero‐stacked graphene/GQDF/SiO2 device, the GQDF plays a role not only as a buffer layer that isolates the CVD graphene from undesired p‐doping of SiO2 substrate but also as a photoactive layer.